Excellent Contemporary Graft Survival for Adult Liver Retransplantation: An Australian and New Zealand Registry Analysis From 1986 to 2017. Issue 8 (August 2019) - Jeffrey, Angus W.; Delriviere, Luc; McCaughan, Geoff; Crawford, Michael; Angus, Peter; Jones, Robert; Macdonald, Graeme A.; Fawcett, Jonathan; Wigg, Alan; Chen, John; Gane, Ed; Munn, Stephen; et al.
Abstract : Background: Liver retransplantation is technically challenging, and historical outcomes are significantly worse than for first transplantations. This study aimed to assess graft and patient survival in all Australian and New Zealand liver transplantation units. Methods: A retrospective cohort analysis was performed using data from the Australia and New Zealand Liver Transplant Registry. Graft and patient survival were analyzed according to era. Cox regression was used to determine recipient, donor, or intraoperative variables associated with outcomes. Results: Between 1986 and 2017, Australia and New Zealand performed 4514 adult liver transplants, 302 (6.7%) of which were retransplantations (278 with 2, 22 with 3, 2 with 4). The main causes of graft failure were hepatic artery or portal vein thrombosis (29%), disease recurrence (21%), and graft nonfunction (15%). Patients retransplanted after 2000 had a graft survival of 85% at 1 year, 75% at 5 years, and 64% at 10 years. Patient survival was 89%, 81%, and 74%, respectively. This was higher than retransplantations before 2000 ( P < 0.001). Univariate analysis found that increased recipient age ( P = 0.001), recipient weight ( P = 0.019), and donor age ( P = 0.011) were associated with decreased graft survival prior to 2000; however, only increased patient weight was significant after 2000 ( P = 0.041). Multivariate analysis found only increased recipient weight ( P = 0.042) and donor age ( P = 0.025) was significant prior to 2000. There was no difference in survival for second and third retransplants or comparing time to retransplant. Conclusions: Australia and New Zealand have excellent survival following liver retransplantation. These contemporary results should be utilized for transplant waitlist methods.